Blue LED light-driven photoelectrocatalytic removal of naproxen from water: Kinetics and primary by-products - Changanaqui, Katherina (2020)
Here, we demonstrate the viability of a ZnO/TiO2/Ag2Se thin-film composite synthesized on FTO to degrade the drug naproxen in aqueous solutions by visible-light photoelectrocatalysis (PEC). The experiments were made with 100 mL of solutions containing 5 mg L-1 drug and 50 mM Na2SO4 at natural pH, using a cell equipped with a Pt wire as cathode and the composite as photoanode exposed to a 36 W blue LED lamp. Total degradation was achieved after 210 min of electrolysis at anodic potential of +1.0 V/Ag vertical bar AgCl. This resulted from the oxidative action of hydroxyl radicals formed via direct anodic water discharge and through mediated water oxidation by photogenerated holes. The degradation rate decreased at higher naproxen concentration, but the treatment efficiency became higher due the deceleration of the parasitic reactions involving hydroxyl radicals. In chloride medium, the photoanode showed a large ability to produce active chlorine, which contributed to the oxidation of the target molecule. LC-QToF-MS analysis of treated solutions revealed the generation of four primary naphthalenic by-products, from which the initial degradation route of naproxen is proposed. (C) 2020 Elsevier B.V. All rights reserved.